Impact of dietary-induced obesity on adrenergic-induced cardiomyocyte damage in rats - Vengethasamy, Leanda; Majane, Olebogeng H.I.; du Toit, Eugene F.; Norton, Gavin R.; Woodiwiss, Angela J. (SA Heart Journal, 2017)
Although obesity is an independent risk factor for heart failure and even mild-to-moderate forms of obesity are associated with myocardial systolic dysfunction the mechanisms of the myocardial dysfunction have not been identifi ed. We assessed whether dietary-induced obesity is associated with an increased sensitivity of the myocardium to ß-adrenergic-induced cardiomyocyte apoptosis or fibrosis. To induce obesity, rats were fed a diet that promotes an increased caloric intake. Adrenergic-induced cardiomyocyte apoptosis was determined by injecting rats for 5 days with isoproterenol (0.01 mg/kg/day for 3 days and 0.02 mg/kg/day for 2 days) and then studying the degree of cardiomyocyte damage using a TUNEL assay and assessing the pathological score. Five months of feeding rats a diet that promoted the development of an increased body weight (Control=481±4.3 g, Diet=550±7.8 g, p‹0.001) and visceral fat content (Control=19.6±0.8 g, Diet=33.0±1.2 g, p‹0.0001), did not alter baseline cardiomyocyte apoptosis. However, 5 days of ß-adrenergic activation resulted in an enhanced cardiomyocyte apoptosis in rats receiving the experimental diet as compared to rats receiving a normal diet (p‹0.01). No changes in the myocardial pathological score (fibrosis) were noted. The enhanced adrenergic-induced cardiomyocyte apoptosis in obese rats could not be explained by dietary-induced increases in baseline left ventricular internal diameters, decreases in systolic function (endocardial or midwall fractional shortening) or differences in the response of the heart to adrenergic-induced increases in inotropic or chronotropic function. In conclusion, the present study suggests that obesity may contribute to myocardial dysfunction by increasing the sensitivity of the myocardium to adrenergic-induced cardiomyocyte damage.